Transparansi Pengelolaan Dana Desa di Desa Balayo Kecamatan Patilanggio Kabupaten - Aiga Doholio; Yanti Aneta; Dwi Indah Yuliani Solihin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to examine and describe the transparency of Village Fund management in Balayo Village, Patilanggio Subdistrict, Pohuwato Regency. The study was motivated by the persistence of issues in implementing transparency principles, particularly regarding the disclosure of information on Village Fund management. Preliminary observations revealed that the village government had not provided adequate information media, such as billboards, information boards, social media platforms, or a village website, accessible to the public for information on the allocation and utilization of Village Funds. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The findings indicate that the transparency of Village Fund management in Balayo Village has not been implemented optimally. First, information has been disclosed through village deliberation meetings; however, limitations in the dissemination media have prevented the community from fully understanding the management of Village Funds. Second, procedural transparency has been implemented relatively well through village deliberation forums that involve community members in the Village Fund management process. Third, the village government has pursued regulatory transparency, although policy and program adjustments are occasionally made in response to specific conditions and circumstances. Fourth, transparency in accommodating community participation is considered fairly good, as community members are involved in village deliberations and development activities. In conclusion, while several aspects of transparency have been implemented, the overall transparency of Village Fund management in Balayo Village remains suboptimal and requires further improvement, particularly in strengthening information accessibility and public understanding of Village Fund governance.